PENGARUH KINERJA MAKROEKONOMI TERHADAP PENANAMAN MODAL ASING DI INDONESIA BAGIAN TIMUR DAN TENGAH - Agustina Suparyati (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2019)
The purpose of this study is to estimate macroeconomic variables consisting of economic growth, rate of increase, labor wages and economic openness to investment in the Indonesian region of East and Central. The analytical method used is multiple regression analysis method with panel data model which is a combination of time series and cross section data. The scope of the study area is 16 provinces consisting of 4 provinces in eastern Indonesia and 14 provinces in central Indonesia in the 2012-2017 period. The results of the multiple regression estimation for panel data indicate that there is only one macroeconomic variable that has a significant influence on foreign investment in eastern and central Indonesia, namely labor wages with a negative correlation, which means the lower the wage level, the higher the investment of foreign capital in the region which shows that low wages are still the main attraction for foreign investment in Eastern and Central Indonesia. Meanwhile, other macroeconomic performance variables, namely economic growth, inflation rates and partial economic openness, do not have a significant effect on FDI. But the results of statistical tests show that statistically it is proven that there is at least one independent variable that has an influence on the dependent variable.